Perilaku Seksual Remaja Sekolah Menengah Atas (SMA) di Kota Pekalongan - Mei Lestariningrum; Harbandinah Pietojo; Syamsulhuda Budi Mustofa (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Teenagers have vulnerable group in reproductive health area. This periode marked by strong disire to try and explore new things including sexual behavior. The aims of this research are finding out the factors influencing on the pre-marital sexual behaviors in senior high school in Pekalongan City. This research is a quantitative research by using the cross sectional approach, as many as 320 respondents ranging from 15 to 20 years old, in which, its method of data collection used structured questionnaire. The research results show that pre-marital sexual 5,9% has a risky toward unwanted pregnancy and an influence variable connecting with pre-marital sexual toward unwanted pregnancy are peers’ role and attitude of sexuality. The teenagers with more permissive attitudes have the tendency of having more risky behaviors 3,87 times greater than those who have less permissive attitudes. The teenagers who have peers’ more permisive have the tendency of doing pre-marital sexual behaviors 4,77 greater than those who have peer’s less permisive.